2008
DOI: 10.4238/vol7-3gmr457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity in jackfruit (Artocarpus heterophyllus Lam.) based on amplified fragment length polymorphism markers

Abstract: ABStrACt. Artocarpus heterophyllus Lam., commonly called jackfruit, is a medium-sized evergreen tree that bears high yields of the largest known edible fruit. Yet, it has been little explored commercially due to wide variation in fruit quality. The genetic diversity and genetic relatedness of 50 jackfruit accessions were studied using amplified fragment length polymorphism markers. Of 16 primer pairs evaluated, eight were selected for screening of genotypes based on the number and quality of polymorphic fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 23 publications
2
42
0
1
Order By: Relevance
“…As an underutilized crop, jackfruit has escaped intensive selection and cultivation. For these reasons, a wide range of genetic and morphological variation has been reported for jackfruit (Azad 1999;Azad et al 2007;Hossain 1996;IPGRI 2000;Jagadeesh et al 2006;Saha et al 1996;Schnell et al 2001;Shyamalamma et al 2008;Ullah and Haque 2008). All of these studies indicate that both within and between population variation exists.…”
Section: Jackfruit Diversitymentioning
confidence: 90%
“…As an underutilized crop, jackfruit has escaped intensive selection and cultivation. For these reasons, a wide range of genetic and morphological variation has been reported for jackfruit (Azad 1999;Azad et al 2007;Hossain 1996;IPGRI 2000;Jagadeesh et al 2006;Saha et al 1996;Schnell et al 2001;Shyamalamma et al 2008;Ullah and Haque 2008). All of these studies indicate that both within and between population variation exists.…”
Section: Jackfruit Diversitymentioning
confidence: 90%
“…B. papyrifera has a wide distribution, but it is scattered in southwest China. Based on ISSR analysis, the overall genetic diversity is relative-ly high at the species level (PPB: 96%) compared with other Moraceae species, such as Ficus carica (PPB: 72.23%) (Salhi-Hannachi et al, 2006), Morus serrata (PPB: 67%) (Vijayan et al, 2004), Artocarpus heterophyllus (PPB: 22%) (Shyamalamma et al, 2008), and Artocarpus altilis (PPB: 85%) (Sreekumar et al, 2007). However, the genetic diversity is relatively low at the population level (PPB: 53.2%, H E : 0.1826, I: 0.2735).…”
Section: Genetic Diversity Of B Papyriferamentioning
confidence: 99%
“…The origin of jackfruit is unclear, but it is likely native to the Indian subcontinent ( Jarrett, 1959 ). Even with morphological descriptors, accurate breadfruit cultivar identifi cation remains diffi cult ( Jones et al, 2013 ), and little is known about jackfruit genetic diversity ( Shyamalamma et al, 2008 ). Despite the fact that breadfruit and jackfruit are in different Artocarpus subgenera ( Zerega et al, 2010 ), several primers cross-amplifi ed well and showed polymorphisms, suggesting they might be useful in additional Artocarpus species.…”
mentioning
confidence: 99%